Prof. Dr. Jorge Bossi (1934-2020): father of modern Uruguayan geology - Gaucher, Claudio; Cingolani, Carlos Alberto; Blanco, Gonzalo; Piñeyro, Daniel; Celio, Antonella; Ribot, Alejandro (Agrociencia Uruguay, 2022)
A synthesis of the academic and scientific activity developed by Prof. Dr. Jorge Bossi, during more than 60 years dedicated to the study of the geology of Uruguay, is offered. This work is a review of his university teaching work and a tribute to his fruitful academic and scientific work on the geology of Uruguay and the region. His contributions have decisively influenced the current understanding of the tectonic evolution, stratigraphy and mineral resources of an important part of South America and southern Africa.